TRENDS IN TOTAL AFLATOXINS AND NUTRITIONAL IMPACT OF TRITICUM SPP DURING FERMENTATION OF KUNUN-ZAKI; A NIGERIA SORGHUM BICOLOR BASED NON-ALCOHOLIC BEVERAGE.: Life Sciences-Microbiology - J.R. WARTU; C.M.Z.WHONG; I.O.ABDULLAHI; J.B. AMEH; B.J.MUSA (International Journal of Life Science and Pharma Research, 2022)
Moulds secondary metabolites such as aflatoxins are carcinogenic when consumed in food and feed. The aim of this research was to assess total aflatoxin decontamination from contaminated wheat-sorghum composite used for ``kunun-zaki`` production. The cereal composite; wholesome Triticum spp and Sorghum bicolor were blended to a different percentage ratio (5, 7.5 and 10 %). Naturally aflatoxin contaminated cereals were also blended with wholesome Sorghum bicolor to 1,2 and 3%. The various blends were batch fermented at ambient temperature in open fermentors to produce Kunun-zaki. Enzyme Linked immunosorbent assay (ELISA) was used to detect and quantify total aflatoxins. Increasing the percentage of naturally aflatoxin contaminated cereal correlated well with increase in total aflatoxin contents. However, there was no significant difference (P>0.05) between the total aflatoxin levels in the different stages of kunun-zaki production. The mean total aflatoxin decontamination was 18.9% and 52.9% for kunun-zaki stored at 4 and 28±2oC. The protein content increased significantly (2.72-4.90%) as the percentage wheat substitution increased from 5, 7.5, and 10%. From this research, aflatoxin decontamination through fermentation of the beverage is not significantly higher and the aflatoxin contaminated cereals could serve as an inoculum of its toxic content into kunun-zaki, consequently, it’s likely health threats to consumers. There is a need for awareness on the quality of raw material for kunun-zaki production.